Elevating Seventh-Grade Students' English Vocabulary Mastery Using Flashcards - Rizqiyah, Fathur; Syaripuddin, Rahmatullah; Purwanti, Eka (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
The low vocabulary mastery of seventh-grade students at MTs Ittihadiyah Tanreassona indicates the need for more effective teaching strategies to enhance language skills. This research aims to investigate the effectiveness of flashcards as a learning media to elevate students' English vocabulary mastery. Employing a pre-experimental design, the study involved 34 seventh-grade students and utilized tests as the primary data collection tool, analyzed using SPSS 26.0. The result posits that flashcards significantly enhance vocabulary retention and recall. The findings confirm that flashcards effectively elevate students' vocabulary mastery by providing an engaging and interactive learning experience.